Differences by age and sex in the sedentary time of adults in Scotland. Issue 7 (3rd April 2018) - Strain, Tessa; Kelly, Paul; Mutrie, Nanette; Fitzsimons, Claire
ABSTRACT: Previous nationally-representative research in Scotland found a j-shaped relationship between age and leisure sedentary time (ST): a decrease from young to middle-age, before rising steeply in older-age. This study investigated the effects of age and sex on weekday (including work) ST for all adults and stratified by work-status, and on weekend day ST. Differences in the relative contributions of component behaviours were also investigated. Responses from 14, 367 adult (≥16 years) 2012–14 Scottish Health Survey participants were analysed using linear regressions. We found no j-shaped relationship between age and weekday ST. Instead, only 16–24 year olds reported lower levels than those over 75 years (6.6 (95% CI: 6.3–6.9) compared to 7.4 (95% CI: 7.2–7.6) hours/day; p < 0001). The j-shape was only evident in the stratified analysis amongst women not in work, and for weekend day ST for all groups. For those in work, work ST accounted for 45% of weekday ST. Television/screen ST made up over half of leisure ST on weekdays and weekend days, regardless of sex, age, or work-status. These results challenge our understanding of how ST varies by age. Interventions to reduce ST should consider differences in the relative contributions of ST behaviours by age and work-status.